Political Party Supporters' Attitudes towards and Involvement with Green Issues in Britain. (December 2014) - Clements, Ben
Recent developments in British politics have seen green issues become a settled part of the policy agenda, with the Conservative-Liberal Democrat coalition pledging to be the 'greenest government ever'. Despite this party political consensus, there has been little recent analysis of attitudes towards green issues among party supporters. Are Conservative supporters less likely to be 'green-minded', in spite of recent efforts to improve the party's image on the environment as part of a wider modernisation strategy? This article provides a detailed assessment using a new nationally representative survey of public opinion on green issues. Based on a wide-ranging analysis of attitudes and behaviour, the findings show that Conservative supporters and those with right-wing policy preferences are less green-minded. Liberal Democrat supporters are the most consistently environmentally friendly in their beliefs and behaviour.